Spectral photokinetic conversion of the fluorescent probes BSB and K114 for improved detection of amyloid assemblies. Issue 12 (19th September 2021) - Stepanchuk, Anastasiia A.; Joseph, Jeffrey T.; Stys, Peter K.
Abstract: Cross‐β‐sheet‐rich protein fibrils are infamous for their accumulation in the brains of patients diagnosed with a number of neurodegenerative diseases, including Alzheimer's disease (AD). Disease‐relevant fibrils are a result of deviation of the proteins from their native structure to a misfolded state resulting in aggregation and formation of fibrils. In this study, we explored the phenomenon of light‐induced fluorescence enhancement of amyloid assemblies stained with two amyloid probes (BSB and K114) using Bombyx mori silk and human AD brain sections. The photoconversion effect, accompanied by an increase in fluorescence intensity and spectral blue‐shift, was highly dependent on the chemical structures of the dyes, pH, presence of glycerol and the type of amyloid. The degree of intensity and spectral change over time in response to high laser exposure were quantified and analyzed using custom‐written analysis tools. Our findings provide further insight into possible mechanisms of amyloid‐mediated photoconversion kinetics of K114 and BSB, and may provide more insight into the molecular nature of various amyloid assemblies. Abstract : Exposure of amyloids stained with BSB and K114 to high laser power resulted in a permanent increase in fluorescence intensity, as well as a spectral blue‐shift. The degree of fluorescence change over time ("photoconversion, " PC) was quantified in different amyloids. The kinetics of photoconversion‐induced intensity and emission changes was found to strongly depend on such factors as dye structure, pH, presence of glycerol and the type of amyloid assembly.